2016
DOI: 10.1007/s10689-016-9900-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and genetic counselor perceptions of in-person versus telephone genetic counseling for hereditary breast/ovarian cancer

Abstract: Telephone genetic counseling (TC) for high-risk women interested in BRCA1/2 testing has been shown to yield positive outcomes comparable to usual care (UC; in-person) genetic counseling. However, little is known about how genetic counselors perceive the delivery of these alternate forms of genetic counseling. As part of a randomized trial of TC versus UC, genetic counselors completed a 5-item genetic counselor process questionnaire (GCQ) assessing key elements of pre-test sessions (information delivery, emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Similar to the aforementioned literature regarding live videoconferencing in genetic services, additional previous genetics literature has also outlined various reasons that telephone services may have an important role to play in genetics, including improving access, timeliness, convenience, and efficiency, and reducing costs (Baumanis, Evans, Callanan, & Susswein, ; Peshkin et al, ; Platten et al, ; Sangha, Dircks, & Langlois, ; Schwartz et al, ; Sutphen et al, ). Further, some studies have suggested similar outcomes when comparing telephone consultations to in‐person care (Buchanan et al, ; Chang et al, ; Fournier et al, ; Jacobs et al, ), and to video consultations (Voils et al, ). Some data also suggest that patients prefer, or are willing to utilize, telephone consultations more so than video consultations (Hardy & Grinzaid, ; Voils et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to the aforementioned literature regarding live videoconferencing in genetic services, additional previous genetics literature has also outlined various reasons that telephone services may have an important role to play in genetics, including improving access, timeliness, convenience, and efficiency, and reducing costs (Baumanis, Evans, Callanan, & Susswein, ; Peshkin et al, ; Platten et al, ; Sangha, Dircks, & Langlois, ; Schwartz et al, ; Sutphen et al, ). Further, some studies have suggested similar outcomes when comparing telephone consultations to in‐person care (Buchanan et al, ; Chang et al, ; Fournier et al, ; Jacobs et al, ), and to video consultations (Voils et al, ). Some data also suggest that patients prefer, or are willing to utilize, telephone consultations more so than video consultations (Hardy & Grinzaid, ; Voils et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…As noted in this study, and in some previous work, there is not a one‐size‐fits‐all approach to telegenetics, and each organization must consider its own goals and needs when defining their chosen telegenetics program model within the expanding field of telehealth models. Interestingly, several studies have pointed to the benefits of patients having some choice in how they receive services, citing the potential for improved attendance, satisfaction, and patient outcomes when patients receive their preferred mode of service delivery (Baumanis et al, ; Jacobs et al, ; Hilgart et al, ). Provider engagement is vital to the field in areas such as professional cooperation, telehealth training, and advocacy for telehealth policy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found support for related technologies, including telephone genetic counseling and technologies that support family communication. Although these studies did not explicitly include DOI measures, findings suggest that characteristics of the innovation led to positive perceptions of the new innovation among genetic counselors (Greenhalgh et al., 2004; Jacobs et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…6 7 These alternatives show high rates of patient satisfaction and similar outcomes in measures of knowledge, psychological functioning and uptake of genetic testing compared with in-person appointments. [8][9][10] Thus, the provision of high-quality genetics services through alternate models of care and the virtualisation of clinical systems was seen as an opportunity to maintain genetic counselling services during the COVID-19 pandemic. While some genetic clinics have shown positive adaptations to the pandemic through rapid implementation of well-established alternative service delivery models, there is a paucity of literature describing virtualisation of genetic teams to physically distance within the Canadian context.…”
Section: Introductionmentioning
confidence: 99%